2021
DOI: 10.1016/j.ajog.2020.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Impact of uterine manipulator on oncological outcome in endometrial cancer surgery

Abstract: BACKGROUND: There are limited data available to indicate whether oncological outcomes might be influenced by the uterine manipulator, which is used at the time of hysterectomy for minimally invasive surgery in patients with endometrial cancer. The current evidence derives from retrospective studies with limited sample sizes. Without substantial evidence to support its use, surgeons are required to make decisions about its use based only on their personal choice and surgical experience. OBJECTIVE: To evaluate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(49 citation statements)
references
References 32 publications
(24 reference statements)
1
32
1
Order By: Relevance
“…Those data have been confirmed in our analysis (Table 5). Again, in a recent retrospective study, Padilla-Iserte et al reported, in a large uterine-confined EC series, that the use of IUM was associated with a worse oncological outcome in patients with uterus-confined endometrial cancer (Figo Stages I-II) who underwent minimally invasive surgery (44).…”
Section: Discussionmentioning
confidence: 97%
“…Those data have been confirmed in our analysis (Table 5). Again, in a recent retrospective study, Padilla-Iserte et al reported, in a large uterine-confined EC series, that the use of IUM was associated with a worse oncological outcome in patients with uterus-confined endometrial cancer (Figo Stages I-II) who underwent minimally invasive surgery (44).…”
Section: Discussionmentioning
confidence: 97%
“…In a prospective study with 46 patients, in which peritoneal washing and cytology were performed before inserting the uterine manipulator, after its insertion and after removal of the uterus through the vagina, it was found that the use of the uterine manipulator was associated with a higher rate of positive peritoneal cytologies [12]. A retrospective, multicentre study carried out in Spain in which data were collected from 2,661 patients, of which 1,756 underwent hysterectomy with a uterine manipulator and 905 without it, found worse oncological results among the first patients: recurrence rate of 11.69% versus 7.4%, lower disease-free survival and higher risk of death [13].…”
Section: Discussionmentioning
confidence: 99%
“…Worse oncological outcomes have been reported in patients presenting with gynecological malignancies in the event of inadequate tumor manipulation. 1 Since the publication of the Laparoscopic Approach to Cervical Cancer trial, 2 the importance of surgical protective maneuvers has been pointed out in the management of early-stage cervical and endometrial cancers. 1 3 These maneuvers aim to prevent tumor exposure and fragmentation, and peritoneal and vaginal spillage by avoiding the use of a uterine manipulator and performing a meticulous vaginal closure over the tumor.…”
Section: Gynecological Cancermentioning
confidence: 99%